WHAT IS A BALANCED CURRICULUM IN ACCOUNTING? - Revzan, David A. (The Accounting Review, 1949)
The author focuses attention on the peculiar aspects of the role of the accounting curriculum in the university, and in the professional school of business. The first characteristic that should be noted is the fact that much of the professional concentration in accounting is dominated by the focusing effects and the control exercised by preparation for the certified public accountants (CPA) examination. Another factor that needs to be noted as an important molding force, is the widespread importance exerted by opportunities in tax and government accounting, particularly for income tax purposes. The importance of the livelihood furnished by this work, together with other widespread opportunities for immediate employment by a wide range of employers, serve undoubtedly to attract many students as majors whose prime concern may be to select a field in which job opportunities are most plentiful. Many of these are not immediately interested in working for the CPA label, although this may become a basic interest later on for purposes of professional advancement.